Advancing total knee replacement surgery Assessment with Wearable Sensors and AI: A Case Study (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2024)
Background: India has a higher prevalence of about 20-24%.of people suffering from osteoarthiritis. Due tothe load effect, forces between two and three times body weight are transmitted across the knee joint during anormal stride, which accounts for the higher risk of OA.A Qualitative Analysis of Decision-Making for Total KneeReplacement in Patients with Osteoarthritis. A cutting-edge wearable sensor system called Fitknees deliversa complex arrangement of motion sensors that are carefully placed on the lower limb. These sensors outlinethorough kinematic data that include gait analysis, muscle strength, knee range of motion, and balance metrics.Objective: Utilizing individualised measurements, using wearable sensors and AI tool to assess preoperativeevaluations and postoperative rehabilitation programs.Results: camping between affected and unaffected side with the normative data provided by the AI.Conclusion:advancement in the medical technologies have made it easier for medial professionals to detect and early diagnosethe diseases. Plan a better treatment plan with the aid of artificial intelligence to achieve better results.
Keywords: OA knee, Total Knee Replacement, wearable sensors, artificial intelligence, advanced diagnostics.